2020
DOI: 10.1007/s00508-020-01739-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a structured exercise program on physical performance and function, quality of life and work ability of physically active breast cancer survivors

Abstract: Summary Background Purpose of this retrospective data analysis was to depict the effects of a structured off-season conditioning program with breast cancer survivors competing in dragon boat paddling. Methods In this study 10 breast cancer survivors (mean age 52.0 ± 5.4 years) who had finished the primary cancer treatment and who were paddlers of the Vienna Pink Dragon self-help group underwent a structured 10-week exercise program as part of their routine supportive treatment. Upper extremity strength, end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The findings of this systematic review complement and extend findings from previous reviews summarizing the effects of psychosocial interventions on body image among women diagnosed with breast cancer 10,14–16 . Sixty‐two articles 22–83 describing 59 studies employing various study methods to evaluate a total of 70 interventions were included in this review. Several findings warrant special attention.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The findings of this systematic review complement and extend findings from previous reviews summarizing the effects of psychosocial interventions on body image among women diagnosed with breast cancer 10,14–16 . Sixty‐two articles 22–83 describing 59 studies employing various study methods to evaluate a total of 70 interventions were included in this review. Several findings warrant special attention.…”
Section: Discussionsupporting
confidence: 57%
“…After removing duplicates ( n = 886), 3309 titles and abstracts were screened; of these, 463 underwent full‐text screening. In total, 62 articles describing 59 studies (with 70 interventions) were eligible and included in this review 22–83 . To provide context for the main results, the next section provides a global narrative overview of the 62 articles.…”
Section: Resultsmentioning
confidence: 99%
“…In an analysis of data from eight European countries up to May 2020 differentiating sex, the progression ratios per 10 years of age of COVID-19 mortality has been estimated as 3.3 and 3.4 for females and males, respectively 14 , which does not indicate any narrowing of the excess risk of men with increasing age. Ahrenfeldt et al 24 for 10 European countries reported crude relative risks for males in four age groups from data collected up to June 29, 2020. They found the smallest differences between males and females in the age group over 85 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Studies report that physical rehabilitation techniques and exercise regimens can help to reduce pain, fatigue, weakness, and lymphedema and thus improve QoL (8). Integrated structured exercise programs have been de ned and prescribed to check their bene ts over the QoL domains (9)(10)(11). In addition, a study reported that while structured exercise programs should focus on improving cardiorespiratory tness and muscular strength during exercise training, these programs should consider physical activity outside of training, if well-tolerated, to potentially further lower fatigue and improve QoL in cancer survivors (12).…”
Section: Introductionmentioning
confidence: 99%